Erratum: Concordance and limits between transcutaneous and arterial carbon dioxide pressure in emergency department patients with acute respiratory failure: a single-center, prospective, and observational study. Issue 1 (December 2015) - Bobbia, Xavier; Claret, Pierre-Géraud; Palmier, Ludovic; Robert, Michaël; Granpierre, Romain; Roger, Claire; Yan, Justin; Ray, Patrick; Sebbane, Mustapha; Muller, Laurent; La Coussaye, Jean-Emmanuel
Abstract After publication of this article (Scand J Trauma Resusc Emerg Med 23:40, 2015), it came to light that an earlier version had been published in error. This erratum contains the correct version of the article, which incorporates revisions made in response to reviewer comments. Additionally, one of the authors was inadvertently omitted from the author list. This author, Justin Yan, has been included in the corrected author list above. Background Transcutaneous CO2 (PtCO2 ) is a continuous and non-invasive measure recommended by scientific societies in the management of respiratory distress. The objective of this study was to evaluate the correlation between PtCO2 and arterial partial pressure of CO2 (PaCO2 ) by arterial blood gas analysis in emergency patients with dyspnoea, and to determine the factors that interfere with this correlation. Methods From January to June 2014, all adult patients admitted to the RR with dyspnoea during business hours were included in the study if arterial blood gas measurements were indicated. A sensor measuring the PtCO2 was attached to the ear lobe of the patient before the gas analysis. Anamnesis, clinical and laboratory parameters were identified. Results Ninety patients with dyspnoea were included (104 pairs of measurements). The median (IQR) age was 79 years (69 – 85). The correlation between PtCO2 and PaCO2 was R2 =.83 (p <.001) but became lower for values of PaCO2 above 60 mm Hg. The mean bias (± SD) between the two methods of measurement (Bland-Altman analysis) was −1.4 mm Hg (± 7.7) with limits of agreement from −16.4 to 13.7 mm Hg. In univariate analysis, PaO2 interfered with this correlation. After multivariate analysis, temperature (OR = 3.01; 95 % CIs [1.16, 7.80]) and PaO2 (OR = 1.22; 95 % CIs [1.02, 1.47]) significantly interfered with this correlation. Conclusions There is a significant correlation between PaCO2 and PtCO2 values for patients admitted to the emergency department for acute respiratory failure. One limiting factor to routine use of PtCO2 measurements in the emergency department is the presence of hyperthermia.